PREREQUISITES FOR THE EMERGENCE OF DEPARTMENTAL ANTICORRUPTION MECHANISMS - Safarov Temur Uktamovich (Scholar Express Journals, 2022)
As a result of the implementation of practices in the field of combating corruption, questions still arise about the proper establishment of the practice of departmental self-control to prevent corruption, for which the prerequisites should be studied, namely the need for mechanisms to establish anti-corruption control.
Keywords: compliance; OECD; FATF; transparency